The Oncogenic Role of APC/C Activator Protein Cdc20 by an Integrated Pan-Cancer Analysis in Human Tumors - Wu, Fei; Sun, Yang; Chen, Jie; Li, Hongyun; Yao, Kang; Liu, Yongjun; Liu, Qingyong; Lu, Jiaju (Frontiers in Oncology, 2021)
The landscape of CDC20 gene expression and its biological impacts across different types of cancers remains largely unknown. Here, a pan-cancer analysis was performed to analyze the role of Cdc20 in various human cancers. Our results indicated that the expression levels of the CDC20 gene were significantly elevated in bladder cancer, breast cancer, colon cancer, rectum cancer, stomach cancer, esophageal cancer, head and neck cancer, kidney cancer, liver cancer, lung cancer, prostate cancer, pancreatic cancer, and uterine cancer. In addition, the expression of CDC20 was significantly and positively correlated with the increase of clinical stages in multiple cancer types, including breast cancer, kidney cancer, and lung cancer, et al. Among 33 cancer subtypes in the TCGA dataset, the high expression of CDC20 was correlated with poor prognosis in 10 cancer types. Furthermore, the abundance of phosphorylated Cdc20 in the primary tumor was elevated and correlated with increased tumor grade. Next, we sought to elucidate the oncogenic role by analyzing its association with immune infiltration. For most cancer types, the CDC20 expression was positively correlated with the infiltration of cancer-associated fibroblasts and myeloid-derived suppressor cells. To further understand its functional activity, we explored the classic Cdc20 downstream substrates, which were found to be mutually exclusive with the expression of Cdc20. Moreover, the pan-cancer analysis of the molecular function of Cdc20 indicated that BUB1, CCNA2, CCNB1, CDK1, MAD2L1, and PLK1 might play a critical role in interaction with Cdc20. The abundance of Cdc20 was further validated at transcriptional and translational levels with a publicly available dataset and clinical tumor tissues. The knockdown of Cdc20 dramatically inhibited tumor growth both in vivo and in vitro. Therefore, our studies delineated the oncogenic role of CDC20 and its prognostic significance at the pan-cancer level and proved its functional activity in Cdc20 high expression cancer types. Our studies will merits further molecular assays to understand the potential role of Cdc20 in tumorigenesis and provide the rationale for developing novel therapeutic strategies.